2008
DOI: 10.1001/archsurg.143.6.538
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Stage IVA Hepatocellular Carcinoma

Abstract: Hypothesis: A subset of patients with stage IVA hepatocellular carcinoma (HCC) and preserved liver function may benefit from hepatic resection. Design: Retrospective review of a prospectively collected database. Setting: An academic tertiary care hepatobiliary unit. Patients: Twenty patients who underwent surgical treatment for stage IVA HCC between July 1998 and October 2004 were identified from the database. Intervention: Intraoperative ablation of HCC nodules was combined with resection in 6 patients (30%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Relatively high recurrence rate is one of the hallmarks of HCC, and aggressive treatment of recurrence using repeat HR, RFA, or TACE can offer satisfactory OS. 26 , 27 The recurrence rate in our cohort was significantly higher among patients with >3 tumors (83%) than among patients with 2 to 3 tumors or with a single large tumor. Patients with >3 tumors are also less likely to be eligible for a second resection, which helps explain why they showed the lowest OS in our study.…”
Section: Discussionmentioning
confidence: 55%
“…Relatively high recurrence rate is one of the hallmarks of HCC, and aggressive treatment of recurrence using repeat HR, RFA, or TACE can offer satisfactory OS. 26 , 27 The recurrence rate in our cohort was significantly higher among patients with >3 tumors (83%) than among patients with 2 to 3 tumors or with a single large tumor. Patients with >3 tumors are also less likely to be eligible for a second resection, which helps explain why they showed the lowest OS in our study.…”
Section: Discussionmentioning
confidence: 55%
“…The use of CDS as a cornerstone treatment of early-stage HCC has evolved over the last 20 years; significant advances in preoperative evaluation, surgical techniques, and postoperative care have reduced the perioperative morbidity and mortality associated with liver surgery [1115]. Mortality after hepatectomy has dropped from approximately 25% in the 1960s to less than 3% today and investigators from high-volume centers report 0% mortality [18].…”
Section: Discussionmentioning
confidence: 99%
“…For hepatic resection, the presence of distant metastasis is generally considered a contraindication[22]. In contrast, in view of the lack of other effective treatment options, surgical resection especially in eastern countries, is still advocated as the treatment of choice for patients with locally advanced HCC which is classified as pT3-4N0M0[22-24]. Ishizawa et al demonstrated that partial hepatectomy provided survival benefits for patients with multiple tumors with Child-Pugh class A cirrhosis[25].…”
Section: Discussionmentioning
confidence: 99%